Histopathology and immunohistochemistry of peripheral neural sheath tumor and perivascular wall tumor in dog - Loures, F. H.; Conceicao, L. G.; Lauffer-Amorim, R. [UNESP]; Nobrega, J. [UNESP]; Costa, E. P.; Torres Neto, R. [UNESP]; Clemente, J. T.; Viloria, M. I. V.; Silva, J. C. P. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2019)
Soft tissue sarcomas (STS) comprise a heterogeneous group of malignancies derived from extra-skeletal mesenchymal tissues that may show similar histopathological changes. Histopathologic patterns suggestive of perivascular wall tumors (PWT) and peripheral nerve sheath tumors (PNST) have been described. This study investigated the histogenesis in a series of 71 cases of canine STS that showed morphological compatibility with what is described for PWT and PNST. Immunohistochemistry analysis were done to CD56, S100, SMA, Desmin, Von Willebrand Factor, NSE and GFAP. Twenty-one cases (29.6%) showed histopathologic features compatible with PWT, 23 cases (32.4%) with PNST and 27 cases (38.0%) shared both histopathological features. By immunohistochemistry, 59 (83.1%) cases showed positivity only for neural markers and 12 (16.9%) had simultaneous positivity for both neural and muscle markers. PNST was the most prevalent neoplasm and none of the cases were positive for muscle markers only. The histopathologic features were not useful to define the diagnosis of PWT, since most tumors were negative for muscle markers but positive for neural markers. Due to this immunoreactivity and the morphologic features, future studies may propose guidelines for the classification of these neoplasms.
Keywords: dog; soft tissue sarcoma